KIN17 modulates the WNT/β-catenin pathway and epithelial mesenchymal transition in non-small cell lung cancer - Panli Peng; Xukai Li; Zhanfeng Su; Hao Chen; Junhong Lv (Scientific Reports)
Abstract KIN17 may impact epithelial mesenchymal transition (EMT) of cancer cells. However, whether KIN17 impacts EMT in non-small cell lung cancer (NSCLC) remains unknown, which was explored in this study. Bioinformatics analyses were conducted to investigate KIN17’s expression pattern, prognostic value in patients of NSCLC and its related genes. The expression of KIN17 was down-regulated in H1299 NSCLC cells and the invasion, proliferation, and migration upon KIN17 knockdown was examined. In addition, the expression of marker proteins of EMT and the Wingless/int1 (WNT1) signaling pathway upon KIN17 knockdown were examined in vitro and in vivo. mRNA and/or protein expression of KIN17 was higher in multiple cancer tissues, especially in NSCLC tissues. Patients of NSCLC with increased KIN17 expression had lowest disease free survival (DFS). The co-expression network of KIN17 enriched pathways revealed links to tumorigenesis and development. KIN17 knockdown in H1299 cells greatly decreased cell invasion, proliferation, and migration. In addition, KIN17 knockdown increased expression of E-cadherin and reduced expression of Vimentin and N-cadherin, which are all markers of EMT. Moreover, KIN17 knockdown in H1299 cells down-regulated the WNT signaling pathway, an inducer of EMT, as evidenced by reduced expression of WNT1 and β-catenin proteins. Finally, KIN17 knockdown significantly reduced tumor growth and down-regulated EMT and the expression of WNT1 and β-catenin proteins in NSCLC xenograft mice. Collectively, KIN17 knockdown suppressed the progression of NSCLC, potentially involving down-regulation of EMT and the WNT/β-catenin pathway.